PENINGKATAN HASIL BELAJAR OPERASI HITUNG CAMPURAN PADA MATA PELAJARAN MATEMATIKA MELALUI PEMBELAJARAN OLAH PIKIR SEJOLI (OPS) SISWA KELAS III SDN 4 TEMPURAN KECAMATAN SAWOO PONOROGO - Ismini, Ismini (Educatio Vitae, 2016)
The study discusses arithmetic operation for third sudent of tempuran elementary school and have a good score in this lesson.The aims of the research  are to improving student achievement, to intoducing Olah Pikir Sejoli methods, to knows teacher achievement, to expand teacher experience about some innovative learning metods. This research is descriptive qualitatif in nature.The data are 20 students of Tempuran elementary school at the third grade were analysized to reveal the four aims of the research as stated above. The result of this research indicated that Olah Pikir Sejoli Methods can improve the studet achievement up to one hundred percents than traditonal methods. Key Words: Mastery of concepts. Olah Pikir Sejoli (OPS) Methods.